Destruction and abandonment practices in La Rinconada, Ambato (Catamarca, Argentina) - (:unkn) unknown (Cambridge University Press, 2017)
Occupation of the Ambato Valley in north-western Argentina ended abruptly in around AD 1200, with destructive abandonment resulting in burnt and collapsed buildings. Analysis of broken pottery sherds from La Rinconada suggests that this may have been the outcome of a deliberate ‘closing’ activity. Re-fitted vessels were found to be largely complete despite extensive fragmentation; two portions of one vessel were 10m apart with a wall in between. Conjoining fragments of other vessels exhibited contrasting effects of thermal alteration, or were associated with lithic objects that may have been used to destroy them, or appeared to have been deliberately arranged. The evidence is altogether indicative of the intentional destruction and deposition of this material immediately prior to the burning of the site.
Fil: Gordillo, Inés. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Fil: Vindrola-Padrós, Bruno. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina. University College London. Institute of Archaeology; Reino Unido.
Keywords: Argentina; Middle Period; Period of Regional Integration; Ceramics; Fragmentation; Deposition; Arqueología